Pelatihan Pengolahan Sampah Organik: Metode Panen Eco-enzym dan Penggunaanya - Puguh Sujarta; Suharno Suharno; Mesak Mantek (Bakti Hayati: Jurnal Pengabdian Indonesia, 2022)
Eco-enzyme is a multifunctional liquid produced from the fermentation of waste or organic waste, brown sugar/sugar, and water. Eco-enzyme is a magic liquid whose benefits are very environmentally friendly, such as in the eco-enzyme production process to produce O3 gas (same as planting 10 trees), one liter of eco-enzyme solution can purify polluted rivers, such as antiseptics and fertilize the soil. This activity has been carried out at SMA Negeri 2 Skanto in 2020, but now it is devoted to the method of harvesting ecoenzymes and their use. The purpose of this activity is to first introduce a training program on organic waste management on eco-enzyme harvesting methods and their use; secondly, through service, it can produce outputs in the form of a national service journal. This activity was held on August 4, 2021 at SMA Negeri 2 Skanto, Keerom. The target audience involved in this activity are high school students. The selection of the target audience is based on the duties and obligations of students to build Adiwiyata High School that loves the environment. The methods used in the implementation of this activity are lectures, simulations and practice of harvesting methods and their use. In conclusion, the participants were enthusiastic and knew about the harvest and the use of ecoenzymes. Based on the results of the evaluation showed that the level of satisfaction of participants was high when viewed from the percentage of all aspects.Keyword: eco-enzym; skanto; adiwiyata; fermentation; enviroment